Teknik Desinfeksi Perendaman dan Penyemprotan Ekstrak Mengkudu (Morinda Citrifolia Liin), Terhadap Perubahan Stabilitas Dimensi Cetakan Alginat - Kadek Ayu Wirayuni; Desak Nyoman Ayu Juniawati (SONDE (Sound of Dentistry), 2020)
Dental material that is often used in dentistry is alginate. Alginate molding material has imbibition properties that absorb water when it comes into contact with water so that the shape is easier to expand and syneresis is the loss of water content through evaporation, causing shrinkage of the alginate mold when left too long in the open air. It is recommended that the printed product be disinfected first to avoid cross infection. One of the herbs that has antibacterial properties is noni. The purpose of this study was to determine differences in immersion and spraying techniques with 0.5% sodium hypochlorite and noni extract 50%, 25% and 12% for 5 minutes. Data were analyzed by ANOVA test. The conclusion of this study is that there is a change in the stability of the dimensions of the alginate mold in the AB (anteroposterior) and BC distance inter junction techniques, at concentrations of 12% and 25%, experiencing a higher increase compared to the concentration of 50% but still within the clinical tolerance limit ie below 0.5%. The spraying technique has a smaller percentage change compared to the immersion technique. There is a change in dimensional stability of alginate molds with a significant difference in the immersion and spraying technique, soaking causes an increase indimensional changes compared to the spraying technique.